Problem : If f (x) = x2 + 3x + 2 and g(x) = 5x + 3, what is the value of:
a) 3f (1)?
b) 3f (x)?
c) g(x)?
d) 2f (x) + 3g(x)?
e) 5f (x) - 3g(x)?

a) 18.
b) 3x2 + 9x + 2.
c) x + 1.
d) 2x2 + 21x + 13.
e) 5x2 + 1.

Problem : If f (x) = 3x - 2 and g(x) = , what is the value of:
a) 2f (x) + 4g(x)?
b) 3f (x) - g(x)?
c) fg(x)?

a) 6x - 4 + .
b) 9x - 6 - .
c) 3 - .

Problem : If f (x) = 2x - 1, g(x) = 3x + 4, and h(x) = 4x, what is the value of:
a) fg(x)?
b) fh(x)?
c) gh(x)?

a) 6x2 + 5x - 4.
b) 8x2 - 4x.
c) 12x2 + 16x.

Problem : If f (x) = x2 - 2 and g(x) = 2x + 1, what is the value of:
a) (f + g)(x)?
b) fg(x)?
c) fog(x)?
d) gof (x)?

a) x2 + 2x - 1.
b) 2x3 + x2 - 4x - 2.
c) 4x2 + 4x - 1.
d) 2x2 - 3.

Problem : If f (x) = (x - 1)2 and g(x) = 4, what is the value of:
a) (f - g)(x)?
b) fg(x)?
c) fog(x)?
d) gof (x)?

a) (x - 1)2 - 4.
b) 4(x - 1)2.
c) 9.
d) 4.

Problem : If f (x) = x2 - 6 and g(x) = 3x + 7, what is the value of:
a) (f + g)(x)?
b) fg(x)?
c) fog(x)?
d) gof (x).

a) x2 + 3x + 1?
b) 3x3 +7x2 - 18x - 42?
c) 9x2 + 42x + 43?
d) 3x2 - 11.